Dinamika Haji Indonesia: Masa Prakolonial Sampai Masa Kolonial - Wulandari, Nuryuana Dwi; Agung, Rendi Marta; Andriyanto (Keraton: Journal of History Education and Culture, 2024)
Indonesia is one of the countries with the largest Muslim population in the world. The purpose of this study is 1) to find out the implementation of the pre-colonial hajj, 2) to find out the implementation of the hajj during the VOC era, 3) to find out the implementation of the hajj during the Dutch colonial era, 4) to find out the hajj according to Snouck Hurgronje's view. This study uses a historical research method with heuristic, interpretation, verification, and historiography steps. The results of this study are as follows: 1) The hajj began in the 15th century, but there has been no evidence to support this, in addition, the hajj began with traders who traded in the Middle East; 2) the rules for carrying out the hajj were tightened because of the VOC's fear that the Nusantara community would be influenced; 3) The emergence of hajj regulations with passports, sufficient financially for people who will go on the hajj and for the families left behind; 4) The Nusantara community went to perform the hajj of their own accord because they would receive the honor.